2022
DOI: 10.3390/f13101654
|View full text |Cite
|
Sign up to set email alerts
|

A 230-Year Summer Precipitation Variations Recorded by Tree-Ring δ18O in Heng Mountains, North China

Abstract: To explore the history of the changes in monsoon precipitation and their driving mechanisms in the context of global warming, climatology studies using tree-ring stable oxygen isotopes (δ18O) were carried out in Shanxi Province, China. Based on a tree-ring δ18O series from Pinus tabulaeformis Carr. on Heng Mountain, a 230-year June‒July precipitation sequence from 1784 to 2013 AD was reconstructed that explained 45% of the total variance (44% after adjusting the degrees of freedom). The reconstructed sequence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Commencing in the 1670s, there was a transition from high to average precipitation levels. Subsequently, North China experienced a recurrent cycle of dry and humid periods, leading to severe drought events, including the Ding‐wu Disaster in the 1870s, as well as significant droughts in 1920s and early (Liu et al, 2022). These droughts affected the northern and southern regions, resulting in widespread famine‐driven migrations (Pei et al, 2018; Zhai et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Commencing in the 1670s, there was a transition from high to average precipitation levels. Subsequently, North China experienced a recurrent cycle of dry and humid periods, leading to severe drought events, including the Ding‐wu Disaster in the 1870s, as well as significant droughts in 1920s and early (Liu et al, 2022). These droughts affected the northern and southern regions, resulting in widespread famine‐driven migrations (Pei et al, 2018; Zhai et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In examining the dry and wet variations in the surrounding areas, it is widely acknowledged that multiple driving mechanisms influence precipitation. Liu et al (2022) suggested a significant negative correlation between the reconstructed precipitation in the Heng Mountains and ENSO. Furthermore, at the decadal scale, it has been determined that the positive phase of the AMO and the negative phase of the PDO may jointly enhance summer precipitation in the Heng Mountains.…”
Section: Discussionmentioning
confidence: 99%